Sawdust-kaolinite composite as efficient sorbent for heavy metal ions - Ogbu, IC; Akpomie, KG; Osunkunle, AA; Eze, SI (Bangladesh Journal of Scientific and Industrial Research, 2019)
The improvement of the adsorption capacity of clay minerals using chemicals though effective is expensive, results in secondary contamination and noxious to the environment. This study was therefore aimed at the development of a new sawdust clay modified adsorbent (SDKC) as an alternative means of improving the adsorption capacity of kaolinite. The adsorbents were characterized by the Fourier transform infrared spectroscopy and X-ray diffraction analysis. Batch sorption was employed to determine the effect of pH, metal concentration, sorbent dose, time and temperature on the removal of Pb (II) and Cd (II) ions from solution by the adsorbents. Optimum operating conditions of pH 6.0, metal concentration 200mg/L, sorbent dose 0.1g was obtained. Equilibrium isotherm analysis indicated the Langmuir, Temkin and Flory-Huggins models to be more suitable than the Freundlich, Dubinin–Radushkevich (D-R). The kinetic data were analyzed using the pseudo-first order, pseudo-second order, the Elovich and intraparticle diffusion models. The analysis revealed that the adsorption process followed pseudo second order model. The calculated thermodynamic parameters showed an endothermic, spontaneous and a physisorption process between both metal ions and the adsorbents. The obtained result of the experiment indicated a significant improvement in the uptake of Pb (II) and Cd (II) ions on the sawdust modified kaolinite adsorbent than the untreated kaolinite clay. This could be utilized as an alternative to chemical treatment methods Bangladesh J. Sci. Ind. Res.54(1), 99-110, 2019